If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13w + 39 = 0 Reorder the terms: 39 + 13w = 0 Solving 39 + 13w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-39' to each side of the equation. 39 + -39 + 13w = 0 + -39 Combine like terms: 39 + -39 = 0 0 + 13w = 0 + -39 13w = 0 + -39 Combine like terms: 0 + -39 = -39 13w = -39 Divide each side by '13'. w = -3 Simplifying w = -3
| y-2=.666x-27 | | 3.3x-4.2=-0.4 | | y-(-5)=-11 | | 11y-7.5-7y=2 | | C=3.50p+550 | | 48+12s= | | 8(e+6)=3(e+33) | | -34+x+36=32 | | (2x+5)=(3x-8) | | 4(2b+-6)+11=8b+-13 | | 1.5y-7=0.5y | | 5+x+x=2x+6 | | y-7=-.5x-(-6) | | 4a+10=8a+2 | | 11x-(6x-5)=110 | | 3x-4y+5z=-1 | | (2x+10)=(7y-8) | | 2x+-8y=-4 | | 4a-10=8a+2 | | -(-2)+10(-6)= | | 10-6x=4+46 | | 10n-10=4+12(n+11) | | -2(-8q+7)+5q= | | 21=4X-9X | | 3x^4+31x^3+56x^2=0 | | -b+3b-2=2-4b+12 | | 5(5x+1)+4=26x+2 | | (2x+5)=(7x-15) | | 38=p-12 | | 2a+5a=49 | | 3g-7+5g=1 | | 2x/3-3x/5=8 |